Ammonia Stress Coping Strategy in a Highly Invasive Ascidian - Chen, Yuqing; Huang, Xuena; Chen, Yiyong; Zhan, Aibin (Frontiers in Marine Science, 2021)
The outbreak of invasive ascidian Molgula manhattensis has negatively affected marine and coastal ecosystems and caused huge economic loss in various industries such as aquaculture. In mariculture systems usually characterized by high ammonia nitrogen, the capacity of M. manhattensis to defend against drastic ammonia elevation plays a crucial role in its survival and subsequent invasions. However, ammonia coping strategies and associated genes/proteins remain largely unknown. Here we investigated rhesus glycoproteins (Rh)-mediated ammonia transport by identifying all Rh proteins and exploring their mRNA expression regulations under ammonia stress. Three types of primitive Rh proteins were identified, and all contained conserved amino acid residues and functional domains. Ammonia stress largely suppressed the expression of immune-related genes, but rapidly induced the increased expression of Rh genes. Ammonia was converted into glutamine as indicated by the increased expression of glutamine synthetase gene, rather than urea as illustrated by the stable expression of arginase gene. Collectively, M. manhattensis mitigates ammonia challenge by enhancing ammonia excretion through Rh channels and detoxifying ammonia into glutamine. Our results provide insights into the molecular mechanisms underlying high tolerance and invasion success to high ammonia environments by invasive ascidians.